Genotypic and Phenotypic Characterization of Fecal Staphylococcus epidermidis Isolates Suggests Plasticity to Adapt to Different Human Body Sites - Garcia-Gutierrez, Enriqueta; Walsh, Calum J.; Sayavedra, Lizbeth; Diaz-Calvo, Teresa; Thapa, Dinesh; Ruas-Madiedo, Patricia; Mayer, Melinda J.; Cotter, Paul D.; Narbad, Arjan (Frontiers in Microbiology, 2020)
Staphylococcus epidermidis is a commensal species that has been increasingly identified as a nosocomial agent. Despite the interest, little is known about the ability of S. epidermidis isolates to adapt to different ecological niches through comparisons at genotype or phenotype levels. One niche where S. epidermidis has been reported is the human gut. Here, we present three S. epidermidis strains isolated from feces and show that they are not phylogenetically distinct from S. epidermidis isolated from other human body sites. Both gut and skin strains harbored multiple genes associated with biofilm formation and showed similar levels of biofilm formation on abiotic surfaces. High-throughput physiological tests using the BIOLOG technology showed no major metabolic differences between isolates from stool, skin, or cheese, while an isolate from bovine mastitis showed more phenotypic variation. Gut and skin isolates showed the ability to metabolize glycine-conjugated bile acids and to grow in the presence of bile, but the gut isolates exhibited faster anaerobic growth compared to isolates of skin origin.